First Observations of Narrowband Stimulated Electromagnetic Emissions at the Pump Frequency Second Harmonic During Ionosphere Interaction Experiments. Issue 16 (30th August 2018) - Yellu, A. D.; Scales, W. A.; Mahmoudian, A.; Bernhardt, P. A.; Siefring, C. L.; McCarrick, M. J.
Abstract: Reported herein are first observations of narrowband stimulated electromagnetic emissions (NSEEs) within ±30 Hz of the second harmonic of the pump wave frequency during ionospheric heating experiments at the High Frequency Active Auroral Research Program facility. The observations are juxtaposed with contemporaneous NSEEs observed within ±30 Hz of the pump wave frequency. The transmit power of the pump wave is linearly increased, and the pump wave frequency is stepped through frequencies near the third electron gyroharmonic frequency during the experiment. The first observation is that there is a transmit power threshold for the occurrence of NSEEs downshifted from the second harmonic of the pump wave frequency. Secondly, when downshifted NSEEs are present at both the pump frequency and its second harmonic, the transmit power threshold for the onset of both are comparable. Third, the frequency offset of the downshifted NSEEs spectral line from the second harmonic frequency is approximately twice the frequency offset of the downshifted NSEEs spectral line from the pump wave frequency when the downshifted NSEEs are present near both the pump and second harmonic frequency. Finally, the NSEEs at the second harmonic of the pump wave frequency are suppressed at pump frequencies very close to the third electron gyroharmonic frequency. Plain Language Summary: Interaction of high‐power high‐frequency (HF) radio waves with the ionosphere produces secondary radio emissions near the transmitter frequency known as stimulated electromagnetic emissions (SEEs). SEEs have been shown to provide critical ionospheric diagnostic information including particle density, temperature, mass, development of turbulence, and ionization layer creation. This work reports on the first observations of SEEs near twice the transmitter frequency, called second harmonic generation (SHG) emissions, using the High Frequency Active Auroral Research Program ionospheric heating facility. The experiments investigated the dependence of these SHG emissions on transmitter power and frequency. These experiments show a distinct transmitter power threshold for SHG that is in line with parametric decay instability development. The SHG emissions are also suppressed near a harmonic of the electron cyclotron frequency. These observed characteristics are in general similar to those observed in laser‐plasma interactions. This opens the window to utilize the wealth of information from laser‐plasma interaction diagnostic techniques developed over the past decades for ionospheric plasma diagnostics for the first time. This work underscores that SHG should be monitored under all circumstances when making SEE measurements to exploit the additional powerful diagnostic information available. Key Points: First observations of narrowband stimulated emissions in second harmonic generation for ionospheric heating Comparable transmitter power threshold for onset of narrowband stimulated emissions at the pump frequency and pump frequency second harmonic Suppression of stimulated emissions at pump frequency and its second harmonic for pumping close to a harmonic of the electron gyrofrequency